2010
DOI: 10.2478/s11658-009-0036-y
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant properties of carnitine in vitro

Abstract: Abstract:Many of the effects of carnitine are ascribed to its antioxidant properties. The aim of this study was to evaluate the antioxidant properties of carnitine in vitro. Carnitine was found to decolorize ABTS•+ , and to protect fluorescein against bleaching induced by AAPH-derived peroxyl radicals and peroxynitrite, thiol groups against oxidation induced by hydrogen peroxide, peroxyl radicals, hypochlorite and peroxynitrite, and erythrocytes against hemolysis induced by peroxyl radicals and hypochlorite. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
3
24
0
4
Order By: Relevance
“…However, we cannot conclude with certainty that this effect was only due to L-carnitine supplementation, since these patients were also treated with protein-restricted diets plus synthetic amino acid formulas. However, numerous in vitro and in vivo studies have reported antioxidant and antiperoxidative effects for L-carnitine, which is able to act as a metal chelator, scavenger of oxygen reactive species, as well as increase enzymatic and non-enzymatic antioxidants levels (Vanella et al 2000;Reznick et al 1992;Derin et al 2004;Rani and Panneerselvam 2002;Solarska et al 2010;Gülçin 2006;Sitta et al 2009). Furthermore, it should be emphasized that because the toxic effects of the accumulating metabolites in MMA and PA patients, the beneficial effects of L-carnitine supplementation, such as correction of secondary carnitine deficiency, removal of short-chain acyl-CoA derivatives, and restoration of intramitochondrial acyl-CoA/CoA ratios, may improve the metabolic status of these patients (Ribas et al 2010a;Walter 2003), contributing to lower levels of oxidative damage observed in MMA and PA patients during treatment.…”
Section: Discussionmentioning
confidence: 97%
“…However, we cannot conclude with certainty that this effect was only due to L-carnitine supplementation, since these patients were also treated with protein-restricted diets plus synthetic amino acid formulas. However, numerous in vitro and in vivo studies have reported antioxidant and antiperoxidative effects for L-carnitine, which is able to act as a metal chelator, scavenger of oxygen reactive species, as well as increase enzymatic and non-enzymatic antioxidants levels (Vanella et al 2000;Reznick et al 1992;Derin et al 2004;Rani and Panneerselvam 2002;Solarska et al 2010;Gülçin 2006;Sitta et al 2009). Furthermore, it should be emphasized that because the toxic effects of the accumulating metabolites in MMA and PA patients, the beneficial effects of L-carnitine supplementation, such as correction of secondary carnitine deficiency, removal of short-chain acyl-CoA derivatives, and restoration of intramitochondrial acyl-CoA/CoA ratios, may improve the metabolic status of these patients (Ribas et al 2010a;Walter 2003), contributing to lower levels of oxidative damage observed in MMA and PA patients during treatment.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to ONOO -, HClO does not induce hemoglobin oxidation; however, it induces marked hemolysis [26,38,48]. It is believed that HClO-induced erythrocyte hemolysis can result from the production of phospholipid chlorohydrins in the cell membrane as well as by formation of nonselective pores [26,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…They can interfere with the oxidation process by reacting with free radicals, chelating free catalytic metals and also by acting as oxygen scavengers [1,2,3]. Different biological models are widely used in order to evaluate efficacy of novel antioxidants and mechanisms of their action [3].…”
Section: Introductionmentioning
confidence: 99%